Financial Distress Dampak Profitabilitas, Rasio Likuiditas Dan Rasio Leverage Terhadap Financial Distress Pada Perusahaan Jasa Sub Sektor Property Dan Real Estate Di Indonesia: Financial DistressIn Indonesia - Sudaryo, Yoyo; Ayu Sofiat, Nunung; Kumaratih, Ita; Kusumawardani, Astrin; Hadiana, Ana (STMIK Komputama Majenang, 2021)
Abstract Financial distress starts from the company's inability to fulfill its obligations. Companies that have consecutively decreased, the company was in financial distress before the bankruptcy occurred.The purpose of this study was to determine the effect of profitability ratios, activity ratios and leverage ratios on financial distress in property and real estate sub-sector service companies listed on the Indonesia Stock Exchange (BEI).The research method used is a quantitative method with descriptive and verification approaches, quantitative research methods are research methods used to examine a particular population or sample. Descriptive research method is used to determine the value of the independent variable, while verification is used to determine the effect of two or more variables.The results showed the average value of each variable as follows: Financial Distress 4.52, Profitability Ratio 0.07, and Activity Ratio 17.13, Leverage Ratio 52.76. The results of the t test of the Profitability Ratio have an effect on Financial Distress, and the Activity Ratio has no effect on Financial Distress, the Leverage Ratio has an effect on Financial Distress. Based on the results of the f test, it shows that the profitability ratio, activity ratio and leverage ratio simultaneously (together) have a significant effect on financial distress. Keywords: Profitability Ratio, Activity Ratio, Leverage Ratio, Financial Distress.